WILLIAM ERNEST HENLEY’S “INVICTUS”: POETIC THEME AND FIGURATIVE LANGUAGES - Priscilla F. Canoy; Michael Vincent S. Casiño; Nathaniel G. Gido; Kirk Vincent G. Ungab (Galaxy International Interdisciplinary Research Journal, 2022)
Poetic language is a symbolic replica that conveys life and the outside world. Understanding oneself and the wider world requires careful study of William Ernest Henley's poem Invictus. The poem skillfully conveys several important details of a line from each stanza carefully and uses them to strengthen the poem's theme, which is not merely obsessed on one keyword. The poetry conveys dignity, fortitude, courage, perseverance, control, and strength. The poem is written from the perspective of a guy who is suffering and is dealing with numerous problems in life that prevent him from leading a fulfilling life. However, despite those circumstances, the spark of hope in his mind and spirit continues to scream from his heart like a call to arms to overcome the challenges in life and once again be in control of his own life. Literary devices are distinct literary strategies that poets and authors employ to make their points. In order to make this poem successful and convey a strong message, Ernest also used a few literary techniques. Metaphor, personification, imagery, and simile were some of the literary devices analyzed in this poem. As a result, persons who experience darkness in their lives, such as depression, can benefit by thinking about this poetry. Beginning with the statement that there is darkness lurking within our lives that is as black as a hole, those sufferings may be our downfall and cause our unavoidable death, but if we confront those horrors head-on with great bravery and effort, it is only be a treat that vanishes like the darkness before dawn.